Infield greenhouse gas emissions from sugarcane soils in Brazil: effects from synthetic and organic fertilizer application and crop trash accumulation. Issue 3 (27th July 2012) - Carmo, Janaina Braga do; Filoso, Solange; Zotelli, Luciana C.; de, Eraclito R.; Pitombo, Leonardo M.; Duarte‐Neto, Paulo J.; Vargas, Vitor P.; Andrade, Cristiano A.; Gava, Glauber J. C.; Rossetto, Raffaella; Cantarella, Heitor; Neto, André E.; et al.
Abstract Bioethanol from sugarcane is becoming an increasingly important alternative energy source worldwide as it is considered to be both economically and environmentally sustainable. Besides being produced from a tropical perennial grass with high photosynthetic efficiency, sugarcane ethanol is commonly associated with low N fertilizer use because sugarcane from Brazil, the world's largest sugarcane producer, has a low N demand. In recent years, several models have predicted that the use of sugarcane ethanol in replacement to fossil fuel could lead to high greenhouse gas (GHG) emission savings. However, empirical data that can be used to validate model predictions and estimates from indirect methodologies are scarce, especially with regard to emissions associated with different fertilization methods and agricultural management practices commonly used in sugarcane agriculture in Brazil. In this study, we provide in situ data on emissions of three GHG (CO2, N2O, and CH4) from sugarcane soils in Brazil and assess how they vary with fertilization methods and management practices. We measured emissions during the two main phases of the sugarcane crop cycle (plant and ratoon cane), which include different fertilization methods and field conditions. Our results show that N2O and CO2 emissions in plant cane varied significantly depending on the fertilization method and that waste products from ethanol production used as organic fertilizers with mineral fertilizer, as it is the common practice in Brazil, increase emission rates significantly. Cumulatively, the highest emissions were observed for ratoon cane treated with vinasse (liquid waste from ethanol production) especially as the amount of crop trash on the soil surface increased. Emissions of CO2 and N2O were 6.9 kg ha−1 yr−1 and 7.5 kg ha−1 yr−1, respectively, totaling about 3000 kg in CO2 equivalent ha−1 yr−1.